A novel long non-coding RNA from NBL2 pericentromeric macrosatellite forms a perinucleolar aggregate structure in colon cancer. Issue 11 (18th April 2018) - Dumbović, Gabrijela; Biayna, Josep; Banús, Jordi; Samuelsson, Johanna; Roth, Anna; Diederichs, Sven; Alonso, Sergio; Buschbeck, Marcus; Perucho, Manuel; Forcales, Sonia-V
Abstract: Primate-specific NBL2 macrosatellite is hypomethylated in several types of tumors, yet the consequences of this DNA hypomethylation remain unknown. We show that NBL2 conserved repeats are close to the centromeres of most acrocentric chromosomes. NBL2 associates with the perinucleolar region and undergoes severe demethylation in a subset of colorectal cancer (CRC). Upon DNA hypomethylation and histone acetylation, NBL2 repeats are transcribed in tumor cell lines and primary CRCs. NBL2 monomers exhibit promoter activity, and are contained within novel, non-polyA antisense lncRNAs, which we designated TNBL (T umor-associated NBL 2 transcript). TNBL is stable throughout the mitotic cycle, and in interphase nuclei preferentially forms a perinucleolar aggregate in the proximity of a subset of NBL2 loci. TNBL aggregates interact with the SAM68 perinucleolar body in a mirror-image cancer specific perinucleolar structure. TNBL binds with high affinity to several proteins involved in nuclear functions and RNA metabolism, such as CELF1 and NPM1. Our data unveil novel DNA and RNA structural features of a non-coding macrosatellite frequently altered in cancer.